Evaluating the Mechanism of Tropical Expansion Using Idealized Numerical Experiments - Hu Yang; Gerrit Lohmann; Xiaoxu Shi; Juliane Müller (Ocean-Land-Atmosphere Research, 2023)
A wide range of evidence reveals that the tropical belt is expanding. Several mechanisms have been proposed to contribute to this expansion, some of which even contradict each other. The study of Yang et al. suggests that the poleward advancing mid-latitude meridional temperature gradient (MTG), originating from enhanced subtropical ocean warming, plays a leading role in driving tropical expansion. However, the abrupt4xCO2 experiment indicates that tropical expansion occurs at a faster rate than is indicated by changes related to ocean temperature rise. The idealized amip4K experiment illustrates that without introducing any ocean warming pattern, uniform ocean surface warming also drives tropical expansion. The results based on these idealized experiments seem to contradict the hypothesis proposed by Yang et al. In this study, we revisit these 2 experiments and show that both experiments actually support the hypothesis that MTG migration is driving tropical expansion. More specifically, in the abrupt4xCO2 experiment, although the rate of ocean warming is relatively slow, the poleward shift of the MTG is as rapid as tropical expansion. In the amip4K experiment, although ocean surface warming is uniform, the heating effect of the ocean on the atmosphere is nonuniform because of the nonlinear relationship between temperature, evaporation, and thermal radiation. The nonuniform oceanic heating to the atmosphere introduces a poleward shift of the MTG within the upper troposphere and drives a shift in the jet streams. By conducting an additional idealized experiment in which tropical expansion occurs under both a migrating MTG and a cooling climate, we argue that the migration of the MTG, rather than global warming, is the key mechanism in driving tropical expansion.